Penggunaan Substrat Glukosa Berbagai Konsentrasi sebagaiSumber Karbon Microbial Fuel Cell Saccharomyces cerevisiae untuk Menghasilkan Energi Listrik - Nurhakim, Muhammad Amal; Kusdiyantini, Endang; Raharjo, Budi (Departemen Biologi, Fakultas Sains dan Matematika, Universitas Diponegoro, 2016)
The increases of human growth causes electrical energy demand’s expantion while the supply decreases drastically. Energy crisis had triggeredalternative renewable energy sourcesdevelopmentto substitutethe use ofoil that had beenmain energy resources for the people. Microorganisms utilization is used to produce electrical by researchers these years as an effort to actualize the goals. The system used is microbial fuel cell (MFC) technology which utilize metabolism activity from microorganisms to produce electrical energy. Microorganismswill perform metabolism bybreaking down glucose into hydrogen (H2) and oxygen (O2).Hydrogen has a role as raw material that used in reduction reaction with oxygen until it releases electron in anoda as electrical flows source. Saccharomyces cerevisiae is an example microorganisms that can utilize for produce electrical energy. This research aims to find optimal concentration for glucose as a carbon source in microbial fuel cell Saccharomyces cerevisiaeto form electrical energy. This research use S. cerevisiae as microorganisms and variation of glucose concentration as a carbon source. Parameters measured in this study is the voltage (mV) and current (mA). Research’s result shows that glucose in 10 % (w/v) concentrate forms higher results in voltage (mV) and current (mA) compare to glucose with 20% (w/v) concentrate and in the concentrate of 30% (w/v) which values each 561,833 mV and 105,133 mA. Analysis of variance with level of confidence 95% shows glucose concentrates don’t react significantly voltage but react significantly on current. Tukey HSD’s test show significant different between current that was formed by glucose in the concentrate of 10% (w/v) compared to glucose in the concentrate of 20% (w/v) and 30% (w/v).Keywords : Saccharomyces cerevisiae, microbial fuel cell (MFC), glucose, electrical energy